2022
DOI: 10.3389/fvets.2022.896581
|View full text |Cite
|
Sign up to set email alerts
|

Histological and hemodynamic characterization of corpus luteum throughout the luteal phase in pregnant and non-pregnant buffalos in relation to nitric oxide levels based on its anatomical determination

Abstract: This study aims to compare the complete growth and development of corpus luteum (CL) in domestic buffalos from day 5 until day 40 after ovulation either in pregnant or non-pregnant animals and whether luteal vascularity (LV) with progesterone (P4) and nitric oxide (NO) could determine luteal functionality or not. Pluriparous buffalos (Bubalus bubalis) were categorized as pregnant (n = 6) or non-pregnant (n = 9) after pregnancy check at day 25. Animals were subjected to ultrasound analysis to determine the CL a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…In line with our findings, feeding male rabbits 5 % MOLE for 84 days decreased MDA while increasing SOD (Jimoh et al 2021). NO is an oxygen-free radical molecule (Daghash et al 2022) that shares in the regulation of spermatogenesis, sperm motility, and maturation (Abdelnaby et al 2021;El-Sherbiny et al 2022b). In agreement with our results, a low NO level plays an essential role in sperm motility (Du Plessis et al 2010), but an increased level of NO decreases sperm motility and viability (Badade et al 2011).…”
Section: Discussionsupporting
confidence: 88%
“…In line with our findings, feeding male rabbits 5 % MOLE for 84 days decreased MDA while increasing SOD (Jimoh et al 2021). NO is an oxygen-free radical molecule (Daghash et al 2022) that shares in the regulation of spermatogenesis, sperm motility, and maturation (Abdelnaby et al 2021;El-Sherbiny et al 2022b). In agreement with our results, a low NO level plays an essential role in sperm motility (Du Plessis et al 2010), but an increased level of NO decreases sperm motility and viability (Badade et al 2011).…”
Section: Discussionsupporting
confidence: 88%
“…The endometrium is a highly dynamic tissue that undergoes several steroid hormone-induced morphological and functional changes during the estrous cycle and pregnancy [77,78]. In this study, the endometrium displayed evident morphological and functional changes owing to hormonal status.…”
Section: Discussionmentioning
confidence: 75%
“…Similarly, studies revealed that L-Arg enhances the delivery of essential nutrients (Fan et al, 1998;Gardner et al, 2001) and increases placental growth (Wu et al, 2004). Moreover, NO and polyamines are critical for angiogenesis, foetal enhancement and placental development (Daghash et al, 2022;Hong et al, 2020;Redmer et al, 2001;. pregnancies with dissenting foetal growth (Jurisic et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies revealed that L‐Arg enhances the delivery of essential nutrients (Fan et al, 1998; Gardner et al, 2001) and increases placental growth (Wu et al, 2004). Moreover, NO and polyamines are critical for angiogenesis, foetal enhancement and placental development (Daghash et al, 2022; Hong et al, 2020; Redmer et al, 2001; Reynolds & Redmer, 2001). The increased serum NO levels in the L‐Arg administered buffalo cows in the present study support the proposed hypothesis and the aforementioned L‐Arg mechanisms of uterine blood flow modulation.…”
Section: Discussionmentioning
confidence: 99%